Effect of Angle of View and Partial Sleep Deprivation on Distance Perception - Baati, Hamza; Chtourou, Hamdi; Moalla, Wassim; Jarraya, Mohamed; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat (Frontiers in Psychology, 2020)
The present study aimed to investigate the effects of intensive effort on egocentric distance perception according to different angles of view after a sleep deprivation at the beginning (SDB) or at the end (SDE) of the night and after a normal sleep night (NNS)). Ten male soccer players (age 22.8±1.3 years; body mass 72.0±10.4 kg; body height 180.0±3.0 cm) performed a repeated-cycling-exercise (RS) (10×6-s maximal cycling with 24-s in-between) after SDB, SDE and NNS. They were asked to estimate three distances (i.e., 15m, 25m and 35m) before and after RS from different angles of view (i.e., in front (0°) and in side (45° left and 45° right)). For the 35m, distance estimation was better during NNS compared to SDB and SDE for the front and the two side angles either before or after RS (p<0.05). Concerning the 25m, distance estimation was better after compared to before RS for the front angle during the NNS session (p<0.05). For 15m, distance estimation was better during NNS than SDB and SDE for the front and the both side angles after RS (p<0.05). We concluded that partial sleep deprivation negatively affected the estimation of the egocentric distance for the three angles of view either at rest or after RS exercise.